Study of Un-slaughtered Chicken Carcass: Organoleptic Changes and Bacterial Growth Pattern - Yulistiani, Ratna (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Un-slaughtered chicken are haram to consume but still exist according to economic motivation of some people. Un-slaughtered chicken are still available in the market due to mortality during chicken growth also in transportation before slaughtering. Un-slaughtered chicken have different characteristics to fresh chicken carcass such as green stomach color, meanwhile it is very difficult to differentiate organoleptically as if the un-slaughtered chicken were processed directly. The purpose of the study was to define the difference between fresh chicken carcass and un-slaughtered chicken carcass through organoleptic detection including color, smell, and texture of chicken carcass after refrigerating, freezing, boiling, frying and without treatment. Also it was aimed to detect early deterioration test by Postma, bacterial growth pattern, and identify the dominant bacteria. The result showed that there was no organoleptically difference between fresh and un-slaughtered chicken carcass after 0, 1, and 2 hours refrigeration, freezing, boiling, frying, and without treatment. Bacterial growth pattern in the fresh and un-slaughtered chicken carcass were almost similar after 1 hour storage. There was different bacterial growth pattern. The un-slaughtered chicken carcass deteriorated faster. Two, 3, and 4 hours stored un-slaughtered chicken carcass had higher number of bacteria and faster bacterial growth. Escherichia coli dan Staphylococcus aureus were the most common bacteria in un-slaughtered chicken carcass.Keywords: un-slaughtered chicken carcass, organoleptic changes, bacterial growth pattern